Avaliação do desempenho de flotação por ar dissolvido no tratamento de efluente de refinaria de óleo de soja - Cecchet, Juliana (2007)
The aim of this work was to value the performance of three types of coagulants, two of them of polichlorate of alum class and one of them was organic, combined to three polyelectrolytes class (anionic, cationic and no ionic) applying the dissolved air flotation (DAF), to viability their use on treatment of effluents of soybean oil refinery. The study was conducted on laboratory scale where first was tested the coagulants on several dosages combined to several bands of pH and three ascension velocities (Va), finding a optimum band of this combination for one of each three batteries. For this, was fixed parameters how time and fast mixed gradient (1 min / 150 s-1), time and slow mixed gradient (10 min / 40 s-1 5 min / 20 s-1), pressure on saturation chamber (450 kPa) and recirculation ratio (30%). Finding the optimum concentration of coagulant (Cc ótima), optimum coagulation pH (pHcoag ótimo) and optimum ascension velocities (Vaótima), fix those parameters and then goes for a variation of polyelectrolyte, testing several dosages and finding a optimum concentrate of polyelectrolyte (Cf ótimo). Finally, with junction of all optimized parameters, was varied de recirculation rate (R) (10, 20 e 30%), choosing the best R and collecting samples for the determination of levels of turbidity, total suspended solids (TSS), volatile suspended solids (VSS), oil and greases (O&G) and chemical oxygen demand (COD) remaining on treated effluent presenting a percentage of remotion COD of 95,4%, 93,7% and 95,1% and O&G of 100%, 94,2% e 99,8% for the batteries 1, 2 e 3 respectively. Despite of being excellent efficiencies of remotion, the treated effluent was not present characteristics for the reuse on the cooling water towers, because its organics load on the raw effluent its too much higher and even with so good levels of remotion, still was necessary a pos treatment to think on reuse.